‘Silence’ as a Strategy during a Corporate Crisis - The Case of Volkswagen’s ‘Dieselgate’ - Stieglitz, S.; Mirbabaie, Milad; Kroll, T.; Marx, J. (Internet Research)

‘Breaking’ News: Uncovering Sense-Breaking Patterns in Social Media Crisis Communication during the 2017 Manchester Bombing - Mirbabaie, Milad; Marx, J. (Behaviour & Information Technology)

Challenges and Opportunities of Artificial Intelligence for Incident Management - Mirbabaie, Milad; Hellmann, M. (Proceedings of the IFIP 8.2 OASIS Workshop on Post-Digitalization 2019)

Collective Identity Formation on Instagram – Investigating the Social Movement Fridays for Future - Brünker, F.; Deitelhoff, F.; Mirbabaie, Milad (Proceedings of the 30th Australasian Conference on Information Systems)

Reducing the Cognitive Load of Decision-Makers in Emergency Management through Augmented Reality - Mirbabaie, Milad; Fromm, J. (Proceedings of the Twenty-Seventh European Conference on Information Systems)

Nudging People to save Energy in Smart Homes with Social Norms and Self-Commitment - Kroll, T.; Paukstadt, U.; Kreidermann, K.; Mirbabaie, Milad (Proceedings of the Twenty-Seventh European Conference on Information Systems)

'Show Me Your People Skills' - Employing CEO Branding for Corporate Reputation Management in Social Media - Mirbabaie, Milad; Marx, J.; Stieglitz, S. (Proceedings of the 14th International Conference on Wirtschaftsinformatik)

The Potential of Augmented Reality for Improving Occupational First Aid - Fromm, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 14th International Conference on Wirtschaftsinformatik)

Impact of Al Activators on Structure and Catalytic Performance of Cr Catalysts in Homogeneous Ethylene Oligomerization – A Multitechnique in situ/operando Study - Grauke, Reni; Schepper, Rahel; Rabeah, Jabor; Schoch, Roland; Bentrup, Ursula; Bauer, Matthias; Brückner, Angelika (ChemCatChem)

The effect of organizational support on whistleblowing behavior - An experimental analysis - Protte, Marius

Was lange währt, wird endlich gut? Vorschau zur erwarteten Rechtsprechung des BFH zur grunderwerbsteuerlichen Konzernklausel - Kittl, Maximilian; Lorenz, Johannes (Deutsches Steuerrecht)

Tax Complexity for Multinational Corporations in South Africa - Evidence from a Global Survey - Hoppe, Thomas; Safaei, Reyhaneh; Singleton, Amanda; Sureth-Sloane, Caren (Tax Simplification - An African Perspective)
This chapter examines the drivers of corporate income tax complexity for multinational corporations in South Africa. Based on unique data from a global survey of tax consultants which was conducted in 2016 by Hoppe et al, novel insights can be provided into the complexity of the South African tax system. The data enable a comparison of South Africa with the global mean of tax complexity, as well as with its major trade and investment partners. It is further possible to distinguish between different areas of tax complexity, ie, tax code complexity (complexity inherent in the different regulations of the tax code) and tax framework complexity (complexity that arises from the features and processes of a tax system). Frequent changes in tax regulations, ambiguity and interpretation, as well as record-keeping, are found to be the most important complexity drivers in the tax code of South Africa. The analysis further highlights that anti-avoidance provisions, such as transfer pricing and controlled foreign corporation rules, are perceived as most complex. With respect to tax framework complexity, the poor disclosure of audit selection criteria, the lack of experience or technical skills of tax officers in the audit process and problems associated with tax refunds appear to be serious concerns. Even though South Africa’s overall tax system complexity does not seem to differ very much from other related countries, a closer look into the details reveals a number of future challenges.

Deep drawing of fiber metal laminates for automotive lightweight structures - Heggemann, Thomas; Homberg, Werner (Composite Structures)
Current challenges in the automotive industry are the reduction of fuel consumption and the CO2 emissions of future car generations. These aims can be achieved by reducing the weight of the car, which further improves the driving dynamics. In most currently mass-produced cars, the body accounts for one of the largest parts by weight, and hence designing a lightweight car body assumes great importance for reducing fuel consumption and CO2 emissions. Extremely lightweight designs can be achieved by using purely composite materials, which are very light but also highly cost intensive and not yet suitable for large scale production due to the necessity of manual processing. A promising approach for the automated, large-scale production of lightweight car structures with a high stiffness to weight ratio is the combination of high strength steel alloys and CFRP prepregs in a special hybrid material/fiber metal laminate (FML) – which can be further processed by forming technologies such as deep drawing. In current research work at the Chair of Forming and Machining Technology (LUF) at the University of Paderborn, innovative manufacturing processes are being developed for the production of high strength automotive structural components made of fiber metal laminates. This paper presents the results of technological and numerical research that is currently being performed at the LUF into the forming of hybrid fiber metal laminates. This paper focuses on the results of basic research and the individual measures (tool, process and material design) necessary for achieving the desired part quality.

Numerical simulation of high-speed joining of sheet metal structures - Meschut, Gerson; Hein, David; Gerkens, Michael (Procedia Manufacturing)

Fatigue life investigation of resistance spot-welded dual-and complex-phase steels using the LWF-KS-II concept - Hein, David; Meschut, Gerson; Tümkaya, Gökhan

Inductive Locating Method to Locate Miniaturized Wireless Sensors within Inhomogeneous Dielectrics - Lange, Sven; Schröder, Dominik; Hedayat, Christian; Otto, Thomas; Hilleringmann, Ulrich (2019 17th IEEE International New Circuits and Systems Conference (NEWCAS))
For the measurement of process data in bioreactors, very small wireless sensors are currently under development to replace the conventional rod probes. The so-called Sens-o-Spheres measure the temperature and in future the oxygen content and the pH of fluids. In order to evaluate the distribution of the measured values within the process, it is necessary to locate the wireless sensors. Because of the small size of the sphere (diameter 8 mm), inhomogeneous ambient media and the size of the reactor (less than 2 m), an inductive locating by magnetic fields with a frequency of f = 13.56 MHz is necessary. Since the behaviour of the magnetic field is very different from that of the electromagnetic wave, new locating methods are required, which are presented in this paper.
Keywords: oxygen content; inhomogeneous ambient media; magnetic field; inductive locating method; miniaturized wireless sensors; inhomogeneous dielectrics; conventional rod probes; Sens-o-Spheres measure; frequency 13.56 MHz

Success Factors for the Consolidation and Anchoring of Digitalisation Projects - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Hochschulforum Digitalisierung (2019). Strategies Beyond Borders – Transforming Higher Education in a Digital Age. Book of Abstracts)

Digitalisierungsstrategien auf dem Prüfstand – eine empirische Untersuchung auf Basis der Grounded-Theory-Methodologie an deutschen Hochschulen - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Teilhabe an Bildung und Wissenschaft)

Stellungnahme der DFG-Kommission zur Evaluierung des Förderprogramms „Fachinformationsdienste für die Wissenschaft“ - Oevel, Gudrun

Special issue: Selected papers of BPM 2017 - Carmona, Josep; Engels, Gregor; Kumar, Akhil; Reichert, Manfred (Information Systems)